AKUNTABILITAS PENGELOLAAN DANA TUGAS PEMBANTUAN PENYEDIAAN AIR MINUM SANITASI TOTAL BERBASIS MASYARAKAT (PAM-STBM) DI DINAS KESEHATAN KABUPATEN SIGI - Suparman, Suparman (Katalogis, 2018)
The research aims to determine and analyze the accountability of fund Management of Community-Based Total Sanitation Drinking Water Supply in Health Department of Sigi District and determine and analyze the cause of absorption of fund for Community-Based Total Sanitation is not 100%. To achieve those aims, the research components are divided into for aspects, namely: preparation, planning, implementation, and the stage of accountability. Type of research is qualitative descriptive with phenomenological approach. Data collecting method is in-depth interview on six informants and secondary data is taken from monthly, semester, and yearly reports. The result highlights that the analysis of fund management of community-based total sanitation drinking water supply in Health Department of Sigi District from preparation planning, implementation, and the stage of accountability has been well-implemented; then, some causes of fund absorption does not reach 100%, among other, due to the remaining honorarium of working unit, the remaining travel expenses, third party waste, and the remaining funds due to a cancellation of one auction package.